Characterization of oocyte- and embryo-specific 5' untranslated regions (UTRs) of mouse mRNAs - Austenová, Alexandra (Jihočeská univerzita, 2020)
To identify, annotate and characterize the oocyte- and embryo-specific 5' UTRs, RNA-seq datasets from various developmental stages of mouse were processed, followed by de novo transcriptome assembly, filtering, and analysis of the length, GC content, presence of uORFs and identification of enriched sequence motifs.
Characterization of oocyte- and embryo-specific 5' untranslated regions (UTRs) of mouse mRNAs
Keywords: genetics; 5' UTR; bioinformatics; oocyte-specific 5' UTR; embryo-specific 5' UTR; genetics; 5' UTR; bioinformatics; oocyte-specific 5' UTR; embryo-specific 5' UTR